2018
DOI: 10.1007/s11655-018-2987-1
|View full text |Cite
|
Sign up to set email alerts
|

Stationary Treatment Compared with Individualized Chinese Medicine for Type 2 Diabetes Patients with Microvascular Complications: Study Protocol for a Randomized Controlled Trial

Abstract: This study will provide evidence of evidence-based medicine for CM treatment in two or multiple microvascular complications caused by T2DM. (Registration No. ChiCTR-IPR-15007072).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Recently, there are some randomized controlled trials (RCTs) conducted to evaluate the efficacy of TCM for CHD and diabetes. [20][21][22][23][24][37][38][39] In diabetic macroangiopathy, there is an ongoing RCT about the efficacy and safety of Shen-Qi Hua-Yu formula in the treatment of diabetic lower extremity artery disease. 17 Besides, recent clinical study has shown that Jiangtang Tongmai capsule could reduce the carotid intima-media thickness and the area of arterial plaque in the treatment of diabetic macroangiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there are some randomized controlled trials (RCTs) conducted to evaluate the efficacy of TCM for CHD and diabetes. [20][21][22][23][24][37][38][39] In diabetic macroangiopathy, there is an ongoing RCT about the efficacy and safety of Shen-Qi Hua-Yu formula in the treatment of diabetic lower extremity artery disease. 17 Besides, recent clinical study has shown that Jiangtang Tongmai capsule could reduce the carotid intima-media thickness and the area of arterial plaque in the treatment of diabetic macroangiopathy.…”
Section: Discussionmentioning
confidence: 99%